Aqueous micellar systems containing Triton X-114 and Pichia pastoris fermentation supernatant: A novel alternative for single chain-antibody fragment purification - Pellegrini Malpiedi, Luciana (2014)
The main goal of this work was to evaluate the feasibility of using aqueous micellar two-phase systems (AMTPS) of Triton X-114 to purify a single-chain antibody fragment (scFv) directly from yeast fermentation supernatant. The coexistence curves of aqueous micellar two-phase systems, highly loaded (up to 90% wt/wt) with the biological feedstock, were determined. Besides, the effect of several additives such as inorganic salts and affinity ligands on the phase separation behavior was investigated. The obtained coexistence curves demonstrated that the assayed surfactant/yeast broth solutions were able to separate into two phases at temperatures lower than 24 C. This information was then utilized to assay scFv partitioning and purification. In general, proteins present in the yeast broth, including the scFv, partitioned to the top, micelle-depleted phase due to its hydrophilic character. When affinity ligands were used, an opposite behavior was observed for scFv due to the uneven partitioning of ligands toward the micellarrich phase. The best purification performances were attained for the system consisting of 4% wt/wt of Triton X-114, 60% wt/wt of yeast fermentation supernatant and the synthetic ligand Fabsorbent™ F1P HF, with a recovery percentage of 88% and a purification factor of 2. These results demonstrate the potential applicability of these systems for designing early steps for scFv purification directly from yeast broth. New perspectives are now open for the use of this methodology for recombinant antibody fragments purification